March 24, 2017

Post a New Question

Posted by on Thursday, March 10, 2011 at 9:05pm.

Thank you for answering the question before bobpursley,
I understand how you did the deriv of inside, outside, but how do I now do the second derivative since you have the extra -18x^2 in the numerator??
Thank you very much! (I suppose I have to brush up on my derivatives)

Posted by KIKSY on Thursday, March 10, 2011 at 8:52pm.

What is the first and second derivative of 3/(1+2(x^3)) ?
im tempted to do the quotient rule, but this looks weird to me...any advice would be greatly appreciated!!

Math - bobpursley, Thursday, March 10, 2011 at 8:55pm
let u=(1+2x^3)

then f= 3u^-1
f'= -3 *u^-2 *u'

but u'= 6x^2

so f'= -3*6x^2 /(1+2x^3)^2

  • Math CONTINUATION OF QUESTION FROM bobpursley - , Thursday, March 10, 2011 at 11:02pm

    I don't think bobpursley is on line, so permit me to continue ...

    from Bob, y' = -18x^2(1+2x^3)-2

    so using the product rule and chain rule combination

    y'' = -18x^2)(-2)(1+2x^3)^-3(6x^2) + (1+2x^2)^-2(-36x)
    = 216x^4(1+2x^3)^-3 - 36x(1+2x^3)^-2
    = 36x(1+2x^3)^-3 [ 6x^3 - (1+2x^3)]
    = 36x(1+2x^3)^-3 (4x^3-1)
    = 36x(4x^3-1)/(1+2x^3)^3

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question